Unified architecture for efficient binary and worst-case optimal join processing - Kaboli, Amirali (The University of Edinburgh, 2025)
Join processing is a fundamental operation in database management systems; however, traditional join algorithms often encounter efficiency challenges when dealing with complex queries that produce intermediate results much larger than the final query output. The emergence of worst-case optimal join (WCOJ) algorithms represents a significant advancement, offering asymptotically better performance by avoiding the enumeration of potentially exploding intermediate results. In this thesis, we propose a unified architecture that efficiently supports both traditional binary joins and WCOJ processing. As opposed to the state-of-the-art, which only focuses on either hash-based or sort-based join implementations, our system accommodates both physical implementations of binary joins and WCOJ algorithms. Experimental evaluations demonstrate that our system achieves performance gains of up to 3.1× (on average 1.5×) and 4.8× (on average 1.4×) over the state-of-the-art implementation of Generic Join and Free Join methods, respectively, across acyclic and cyclic queries in standard query benchmarks.
A unified architecture for efficient binary and worst-case optimal join processing
Keywords: Unified Architecture; Binary Joins; Worst-case Optimal Join (WCOJ); Efficiency; Performance Gains